2020
DOI: 10.3390/su12187774
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of House Valuation Automation in the Czech Republic

Abstract: Valuation of single-family detached houses is necessary when determining the amounts of some taxes. The current systems of the Czech Republic are outdated in this respect, and they are based on procedures used in the 1980s. The values found do not correspond to current market conditions very often. This article attempts to verify the applicability of a methodology where the value of a detached house is decomposed into the value of the land and the value of the object as such when considering wear. For verifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Additionally, it helps to understand the relationships among the technical condition determinants and their correct use. The preference for selling prices makes this different from other works focused on price-setting factors (Özsoy and S ahin, 2022;Gordon and Winkler, 2016;Khezr, 2015;Hui and Yu, 2012;Endel et al, 2020).…”
Section: H2mentioning
confidence: 83%
See 1 more Smart Citation
“…Additionally, it helps to understand the relationships among the technical condition determinants and their correct use. The preference for selling prices makes this different from other works focused on price-setting factors (Özsoy and S ahin, 2022;Gordon and Winkler, 2016;Khezr, 2015;Hui and Yu, 2012;Endel et al, 2020).…”
Section: H2mentioning
confidence: 83%
“…In the context of market value, houses are very specific assets representatives of the real estate sector, unlike classic commercial products (Endel et al , 2020; Wickramaarachchi et al , 2021), and form a heterogeneous market (Nam, 2020; Cupal, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Assessments of residential property are generally considered as tasks that can be performed with a relatively high level of confidence. This is one of the reasons that there have been a significant number of studies on residential property valuation reported in the literature (Iii et al, 2002;Frew and Jud, 2003;Endel et al, 2020). In contrast, licensed appraisers and valuation modeling experts seem to accept that valuation of (vacant) land is a more delicate assignment (Demetriou, 2018).…”
Section: Property Valuationmentioning
confidence: 99%
“…This is one of the reasons that there have been a significant number of studies on residential property valuation reported in the literature (Iii et al. , 2002; Frew and Jud, 2003; Endel et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is convenient to process structured data using numerical models. The most common input data for house valuation include the number of rooms, floor area and year of build (Endel et al , 2020), all of which are categorized as structured data. In contrast, unstructured data such as images and free-form texts are difficult-to-process variables that cannot be directly utilized in valuation.…”
Section: Introductionmentioning
confidence: 99%